Weekly vinorelbine and paclitaxel in older patients with advanced non-small cell lung cancer: A phase II Fred and Pamela Buffet Cancer Center Clinical Trials Network study. Issue 1 (January 2017) - Huerter, Mary M.; Meza, Jane L.; Copur, M. Sitki; Tolentino, Addison; Marr, Alissa S.; Ketcham, Marsha; DeSpiegelaere, Holly; Kruse, Susan; Kos, Mary E.; Swenson, Karin; Radniecki, Sarah E.; Kessinger, Anne; et al.
Abstract: Objective: Platinum-based doublet chemotherapy is the standard for most patients with advanced non-small cell lung cancer (NSCLC). Toxicity concerns limit chemotherapy for patients over 70 years. Vinorelbine and paclitaxel are effective as single agents in advanced NSCLC. This phase II study evaluates safety and efficacy of a combination of these two agents in patients > 70 years with advanced NSCLC. Materials and Methods: Patients with treatment naïve metastatic NSCLC received two cycles comprising 6 weekly doses of vinorelbine and paclitaxel, with restaging scans at week 8. Patients with radiographic progression came off study. The estimated sample size was 29. Toxicity analyses were conducted after 10 patients and again after 19 patients were enrolled. Outcomes were safety and efficacy, progression free (PFS) and overall survival (OS) and quality of life (QOL). Results: The study closed at second interim analysis as 6/19 patients had ≥ grade 4 non-hematologic toxicity (respiratory failure, sepsis, ischemic encephalopathy, pneumonia, hypoxemia, cardiopulmonary arrest, neutropenic fever, death). Of the 16 evaluable patients, 7 completed the study. Disease control rate (partial response + stable disease) was 47% (n = 9); 37% (n = 7) progressed. No complete responses were seen. Median PFS was 3.5 months (95% CI: 1.4, 5.5) and OS 7.8 months (95% CI: 1.9, 13.6). QOL did not change compared to baseline, at week 9, but increased at week 17. Conclusions: Although the combination met its response end points, increased toxicity makes this combination unsuitable for older patients. While QOL improved over the study, the small sample hinders interpretation.